Egaliterianisme Dalam Pandangan Islam: Potret Pemenuhan Hak Sipil Penghayat Kaharingan - Salmah, Syarifah; Shapiah, Shapiah (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2022)
Islam with its monotheistic teachings is very tolerant of differences in religious beliefs. We must show the equality to all people of all religions and beliefs. This article describes how Islam views egalitarianism by referring to the portrait of the fulfillment of rights for Kaharingan adherents in Palangka Raya City. This study used descriptive qualitative method. Kaharingan integration into Hindu Kaharingan provides convenience for its adherents. This convenience can be enjoyed by Kaharingan adherents because Hinduism is one of the religions recognized by the state, so that it has an impact on the ease of state administration. The fulfillment of the civil rights of adherents of the Kaharingan adherents cannot be separated from the role of the Kaharingan Hindu Religious Council (MBAHK) which is a bridge between its adherents and the government. With the integration process of Kaharingan into Hinduism, all basic rights of Kaharingan adherents can also be fulfilled by the state properly.   Islam dengan ajaran tauhidnya sangat toleran terhadap perbedaan keyakinan beragama. Kita harus menunjukkan kesetaraan kepada semua orang dari semua agama dan kepercayaan. Artikel ini memaparkan bagaimana Islam memandang egalitarianisme dengan merujuk pada potret pemenuhan hak bagi penganut Kaharingan di Kota Palangka Raya. Penelitian ini menggunakan metode kualitatif deskriptif. Integrasi Kaharingan ke dalam Hindu Kaharingan memberikan kemudahan bagi penganutnya. Kemudahan tersebut dapat dinikmati oleh penganut Kaharingan karena agama Hindu merupakan salah satu agama yang diakui oleh negara, sehingga berdampak pada kemudahan penyelenggaraan negara. Pemenuhan hak-hak sipil penganut Kaharingan tidak lepas dari peran Majelis Agama Hindu (MBAHK) Kaharingan yang menjadi jembatan penghubung antara penganutnya dengan pemerintah. Dengan proses integrasi Kaharingan ke dalam agama Hindu, semua hak dasar penganut Kaharingan juga dapat dipenuhi oleh negara dengan baik.